“Positivization” of postmodern interpretation of religion and faith in the work of Merold Westphal - Shevchenko, Serhii (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2018)
The article analyzes the specificity of the correlation between postmodernist and post-existentialist thinking in the context of rethinking S. Kierkegaard ideas in the philosophy of the religion of M. Westphal. Characterized by the features of the concept of “posi-tive postmodernism” by M. Westphal, which offers an informal version of the relationship of reasonand faith in our time. The essence of the methodological understanding of the American theologian “hermeneutics of endurance” and “hermeneutics of suspicion” is revealed, which, on the one hand, are intended to remind a person that he is not God, and on the other – to prevent the disappearance of man with its existential and psycho-emotional problems with contemporary theological thinking. It is argued that the post-existentialist version of the existential theology of M. Westphal, although theoretically “intertwined” in the context of modern postmodernist thought, is in fact the opposite of the position of the wing of postmodernists, which, according to the American thinker, are trying to build a world free from moral obligations and divine grace